(х-4)³+27=(х-4)³+3³=(х-4+3)((х-4)²-3(х-4)+3²)=(х-1)(х²-8х+16-3х+12+9)=(х-1)(х²-11х+37) ну и если надо =х³-11х²+37х-х²+11х-37=х³-10х²+48х-37
ответ: (х-1)(х²-11х+37).
Объяснение:
По формуле сокращённого умножения а³+в³=(а+в)(а²-ав+в²).
(х-4)³+27=(х-4)³+3³=(х-4+3)((х-4)²-3(х-4)+3²)=
=(х-1)(х²-8х+16-3х+12+9)=(х-1)(х²-11х+37).
х²-11х+37=0;
D=121-4*1*37=121-148= -27, D <0 , корней нет.
х²-11х+37 нельзя разложить на множители.
ответ:(х-1)(х²-11х+37).
(х-4)³+27=(х-4)³+3³=(х-4+3)((х-4)²-3(х-4)+3²)=(х-1)(х²-8х+16-3х+12+9)=(х-1)(х²-11х+37) ну и если надо =х³-11х²+37х-х²+11х-37=х³-10х²+48х-37
ответ: (х-1)(х²-11х+37).
Объяснение:
По формуле сокращённого умножения а³+в³=(а+в)(а²-ав+в²).
(х-4)³+27=(х-4)³+3³=(х-4+3)((х-4)²-3(х-4)+3²)=
=(х-1)(х²-8х+16-3х+12+9)=(х-1)(х²-11х+37).
х²-11х+37=0;
D=121-4*1*37=121-148= -27, D <0 , корней нет.
х²-11х+37 нельзя разложить на множители.
ответ:(х-1)(х²-11х+37).